Online water quality monitoring: a case study in the umbulan drinking water supply system, East Java, Indonesia - Rahim, Jusman; Sunarsih, Sunarsih; Budiati, Lilin (Intelektual Pustaka Media Utama, 2024)
Conventional systems that monitor the supply system periodically are considered to be very inadequate. This can cause the water supply distributed to the community to be of poor quality. Therefore, this study aims to evaluate water quality periodically by measuring water parameters such as pH, chlorine and turbidity for 30 days using an online system and portable unit. Portable tools used to measure pH, turbidity and residual chlorine are as follows, namely pH meters (Hanna, HI98017), Turbidity Meters (Hanna, HI 98703), Residual Chlorine meters and measurements with an online system using